Relationship between Apoptosis and E-cadherin Expression in Bronchial Epithelium of Smoking Mouse - 刘丽芳 袁永辉 李钫 刘红云 (Current medical science, 2003)
To investigate whether apoptosis is associated with cell adhesion in bronchial epithelium,and whether it contributes to the kinetics of injury and repair of surface epithelia, this study was performed for E-cadherin expression by using immunohistochemistry technique and for apoptosis by TUNEL method. An animal model of smoking was used for this study. The results showed that epithelial cells with membrane anchored E-cadherin decreased remarkably at several time points during 6 months of exposure to smoke (P<0. 01) and then restored to normal level. This fluctuation was associated exclusively with the alteration in number of apoptotic cells (P<0. 01). There wasno significant difference in activation of nuclear transcription factor NF-kappa B among groups (P>0. 05). All these suggested that apoptosis is associated with E-cadherin expression in bronchial epithelium of smoking mouse.